Pengaruh Promosi, Kemudahan, dan Manfaat Terhadap Keputusan Penggunaan Transfer Shopeepay Mahasiswa FEBI IAIN Ponorogo - Wulandari, Felianti Dwi; Ulya, Husna Ni’matul (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
One of the most popular types is e-wallet is ShopeePay. ShopeePay is the first and largest digital payments in Indonesia. ShopeePay continues to add to its product innovations, one of the innovations is the transfer feature to various banks. This study aims to determine the effect of promotion, convenience and benefits on the decision to use ShopeePay transfers for FEBI IAIN Ponorogo students. This research is classified as quantitative research. The population in this study were FEBI IAIN Ponorogo students with a sample size of 100 students, who had used the ShopeePay transfer feature. The sampling technique used Cochran using multiple linear regression analysis methods using the SPSS 25 program. The results showed that the influence of promotion, convenience and benefits had a significant effect on the decision to use the ShopeePay transfer for FEBI IAIN Ponorogo students. Then from the test results the coefficient of determination (R2) shows that perceived promotion, perceived convenience and perceived benefits affect interest in use by 45%, the remaining 55% is influenced by other factors / variables outside this research.